2012
DOI: 10.1111/j.1746-1561.2012.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Life Skills Into a Theory‐Based Drug‐Use Prevention Program: Effectiveness Among Junior High Students in Taiwan

Abstract: Study results demonstrated the effectiveness of a drug-use prevention program integrating the TPB and life skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…The contents and learning activities of the drug use prevention program were described in detail in our previous report [13]. The TPB/life skills school-based intervention program was designed by our research team by following the seven evidence-based quality criteria for developing an intervention program for drug use prevention [16].…”
Section: Drug Use Prevention Programmentioning
confidence: 99%
See 3 more Smart Citations
“…The contents and learning activities of the drug use prevention program were described in detail in our previous report [13]. The TPB/life skills school-based intervention program was designed by our research team by following the seven evidence-based quality criteria for developing an intervention program for drug use prevention [16].…”
Section: Drug Use Prevention Programmentioning
confidence: 99%
“…Table 1 summarizes the contents and learning activities of the booster sessions. The program contents and learning activities of the booster interventions were designed on the basis of the results of the pilot study we published previously [13], and furthermore modified on the basis of the outcome of in-depth interviews with selected participants of the pilot study 3 months after it was completed. The first booster comprised four 45-minute sessions and homework exercises, whereas the second booster comprised two 45-minute sessions and homework exercises.…”
Section: Intervention and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that life skills programs aimed at the prevention of adolescent substance use can have a positive influence in terms of bonding in a school context (23). Huang et al found that training in life skills can act as a protective factor and decrease drug use in later year (24). Considering the importance of psycho-social strengthening and its role in reducing high-risk behaviors, it is better to start this type of intervention at school from an early age, which is likely to lower the risk of substance use and have a lasting preventative effect.…”
Section: Introductionmentioning
confidence: 99%